2010
DOI: 10.1111/j.1365-313x.2010.04361.x
|View full text |Cite
|
Sign up to set email alerts
|

A replication stress-induced synchronization method for Arabidopsis thaliana root meristems

Abstract: SUMMARYSynchronized cell cultures are an indispensable tool for the identification and understanding of key regulators of the cell cycle. Nevertheless, the use of cell cultures has its disadvantages, because it represents an artificial system that does not completely mimic the endogenous conditions that occur in organized meristems. Here, we present a new and easy method for Arabidopsis thaliana root tip synchronization by hydroxyurea treatment. A major advantage of the method is the possibility of investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 38 publications
6
71
0
Order By: Relevance
“…Recently, gene expression inventories have been collected that focus on the transcriptional changes in response to different types of DNA stress (Culligan et al, 2006;Ricaud et al, 2007;Yoshiyama et al, 2009;Cools et al, 2010). To identify novel key signaling components that contribute to cell cycle checkpoint activation, we compared bleomycin-induced genes to those induced by HU treatment (Cools et al, 2010) and g-radiation (Culligan et al, 2006;Yoshiyama et al, 2009). Twenty-two genes were upregulated in all DNA stress experiments and can be considered as transcriptional hallmarks of the DNA damage response, regardless of the type of DNA stress ( Figure 1, Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, gene expression inventories have been collected that focus on the transcriptional changes in response to different types of DNA stress (Culligan et al, 2006;Ricaud et al, 2007;Yoshiyama et al, 2009;Cools et al, 2010). To identify novel key signaling components that contribute to cell cycle checkpoint activation, we compared bleomycin-induced genes to those induced by HU treatment (Cools et al, 2010) and g-radiation (Culligan et al, 2006;Yoshiyama et al, 2009). Twenty-two genes were upregulated in all DNA stress experiments and can be considered as transcriptional hallmarks of the DNA damage response, regardless of the type of DNA stress ( Figure 1, Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is noteworthy that their expression patterns in roots were not similar. For example, strong expression of UVI4 and CDKB1;1 was detected in root meristems (Hase et al, 2006;Cools et al, 2010), and expression of UBP14 was observed in the root meristem and differentiated regions (Supplemental Figure 15). By contrast, CCS52A1 was expressed around the transition zone, but not in root meristems (Vanstraelen et al, 2009).…”
Section: A Possible Genetic and Molecular Mechanism For Ubp14-mediatementioning
confidence: 99%
“…We thus compared the expression level of several cell cycle-related genes in the wild type and jhs1 mutant. Specifically, we evaluated the expression of CYCB1:1, which is induced at the G 2 phase and encodes a kinase protein with activity that peaks at the G 2 /M transition (Cools et al, 2010); CYCD4:1, which encodes a protein that is expressed from the G 2 to M phase and binds to and activates CDKB2;1 (Kono et al, 2003); CDKA;1, which is required for cell cycle regulation during pollen, embryo, root, and leaf development in Arabidopsis (Dissmeyer et al, 2009); CYCD3;3, which is expressed in the G 1 phase (Menges et al, 2005); histone H3.1 and histone H4, which are specifically expressed in the S-phase (Menges et al, 2003;Yin et al, 2009); CYCA3;1, whose transcripts are highly accumulated at the G 1 /S phase (Juraniec et al, 2016); CYCB1;2 and MAD2, which are markers for G 2 /M phase (Menges et al, 2005;Juraniec et al, 2016) and CYCA2;1, which is induced during the S phase and peaks at the end of the G 2 phase (Shaul et al, 1996), using qRT-PCR analysis (Fig. 9A).…”
Section: The Frequency Of Homologous Recombination Is Increased In Jhs1mentioning
confidence: 99%